Pengaruh metode latihan small sided games terhadap keterampilan passing pada permainan futsal - Halimah, Siti; Sumarsono, Rhama Nurwansyah; Purbangkara, Tedi (Jurnal Porkes, 2023)
The problem in this study is the lack of maximum technical training and passing skills. the purpose of this study was to determine the effect of the small sided games training method on passing skills. quantitative experimental method. The research design used pre-experimental designs one group pretest-posttest. The population consisted of 30 children in grades 10 to 12. This study used a purposive sampling technique. The instrument or measuring device used in this study was the low ball passing test which was tested again and adjusted for the futsal passing test. Instruments used in the form of tests and measurements. Data analysis techniques used descriptive statistics, normality test, homogeneity test, paired sample t-test. The results obtained by data analysis and hypothesis testing from the average before treatment and after treatment experienced a significant increase from 6.03 to 7.83. Meanwhile, the results of the calculation of hypothesis testing obtained a significance value that is less than the significant level (α), namely 0.000 <0.05. Based on the results of descriptive statistical calculations on the mean pretest and posttest passing, it can be concluded that there is an influence of the small sided games method in improving passing skills in futsal extracurricular activities at SMAN 1 Lemahabang.